2019
DOI: 10.1093/cercor/bhz169
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cortico-Cerebellar Structural Connectivity on Cortical Excitability in Chronic Stroke

Abstract: Brain imaging has recently evidenced that the structural state of distinct reciprocal cortico-cerebellar fiber tracts, the dentato-thalamo-cortical tract (DTCT), and the cortico-ponto-cerebellar tract (CPCeT), significantly influences residual motor output in chronic stroke patients, independent from the level of damage to the corticospinal tract (CST). Whether such structural information might also directly relate to measures of cortical excitability is an open question. Eighteen chronic stroke patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 79 publications
2
32
0
Order By: Relevance
“…Previous DTI studies also showed decreased FA in the midbrain of stroke patients by manually plotting ROIs (Wei et al, 2019). A recent study indicated that the cerebellum plays a role in residual motor output by facilitating cortical excitability in chronic stroke (Guder et al, 2020). Taken together, these ndings suggest that the inability to perform normal movements might gradually lead to abnormal balance, which is re ected in decreased cortico-cerebellar connectivity in these patients.…”
Section: The Cerebellummentioning
confidence: 80%
“…Previous DTI studies also showed decreased FA in the midbrain of stroke patients by manually plotting ROIs (Wei et al, 2019). A recent study indicated that the cerebellum plays a role in residual motor output by facilitating cortical excitability in chronic stroke (Guder et al, 2020). Taken together, these ndings suggest that the inability to perform normal movements might gradually lead to abnormal balance, which is re ected in decreased cortico-cerebellar connectivity in these patients.…”
Section: The Cerebellummentioning
confidence: 80%
“…Previous DTI studies also found a decrease in FA in midbrain after stroke by manually plotting ROI [38]. A recent study found the role of the cerebellum for residual motor output by facilitating cortical excitability in chronic stroke [45]. The changes of cortico-cerebellar structural connectivity was probably caused by brain injuries related to the neural bers connecting to cerebellum, but the inability of normal movement may gradually lead to abnormal balance that re ected in the decreases of cortico-cerebellar connectivity.…”
Section: Cerebellummentioning
confidence: 90%
“…The CPT is associated with hand dominance-related alterations ( Kim et al, 2019 ). In addition, previous researches have demonstrated that the integrity of the CPT in patients with chronic stroke affects the residual upper limb function ( Schulz et al, 2015 ; Guder et al, 2020 ). A positive association was observed between the FA of the left FPT and the upper limb sub-score, which concurs with the association between the FA of the CPT and the finger-tapping-score in ALS patients ( Kalra et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%